LANGUAGE AND COGNITION: NEURAL MECHANISMS, EMOTIONAL PROSODY, AND THE INTERACTION BETWEEN LANGUAGE AND THOUGHT - Damanik, Jerico Devaly; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
The relationship between language and cognition continues to be a prominent and complex issue in cognitive science and neuroscience. While there has been substantial progress in understanding the neural networks responsible for language and cognitive processes, many questions remain unresolved. This article explores the neural mechanisms behind language acquisition, its interaction with cognition, and how emotional prosody—elements like pitch, rhythm, and tone—affects language development. The study also investigates the interaction between language and thought, emphasizing the hemispheric specializations for language and cognition. Using advanced brain imaging technologies such as fMRI, this work analyzes the functional connectivity between various language-related and cognitive brain regions, underscoring their recursive interactions. The article concludes by examining how our understanding of language informs cognitive theories, contributing to a greater comprehension of the human mind.